The effectiveness of digital stimuli in improving attention among students with mental disabilities - Althaghafi, Osama Musa (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify the effect of using digital stimuli on improving attention among students with mental disabilities. The study population consisted of fifth grade students in Jeddah. The sample size was 20 randomly selected students. The digital stimuli that contribute to stimulating and improving attention. One of the most important findings of the study: that the digital stimuli represented in the leaderboard pattern have an effective effect on the level of achievement of the mentally handicapped, which indicates the effectiveness of the Kahoot program in increasing the focus of attention. It also showed that using the badge pattern as one of the digital stimuli helps focus attention, which also enhances the effectiveness of the program as one of the gamification programs used in education. The study also confirmed the effectiveness of the dots pattern in reducing distraction, which has a positive effect on increasing the focus of attention.